Developing a curriculum for the teaching of robotics in general education - Lapov Padovan, Zvonimir; Kovačević, Stjepan; Purković, Damir (Polytechnica, 2018)
Over the last few decades, robotics has become an important field of technology which is rapidly evolving and without which modern manufacture cannot be imagined today. Such development also affects the educational process, which needs to be adjusted in order for the society to move forward. Due to the attractiveness and wide availability of various robotic and automated devices and gadgets, robotics has become a subject of interest for children of different ages, as well as the school subject taught in various schools and incorporated in out-of-school programs and activities. Nevertheless, given the complexity and multidisciplinary nature of such content and the high cognitive demands placed on learners, there are problems related to the adequacy of approaches, strategies and methods used in the learning and teaching of robotics, as well as the issues concerning the development and operationalization of robotics curriculum. Therefore, this paper is a theoretical and practical starting point for introducing such teaching and developing an appropriate curriculum. The theoretical part of the paper deals with the importance and role of technology in general education, discusses some theoretical concepts and examines the approaches to the development of technology education in general and the teaching of automatics and robotics in particular. The second part of the paper provides guidelines for the development and operationalization of such curriculum in general education, and outlines a proposal for a curriculum framework. Despite the fact that in these guidelines, a number of student activities are not explained at the micro level, they represent a clear starting point for developing and operationalizing the curriculum that each teacher has to adapt to their students and the environment.